Inflammation and Oxidative Stress in Obesity-Related Glomerulopathy - Jinhua Tang; Haidong Yan; Shougang Zhuang (International Journal of Nephrology)
Obesity-related glomerulopathy is an increasing cause of end-stage renal disease. Obesity has been considered a state of chronic low-grade systemic inflammation and chronic oxidative stress. Augmented inflammation in adipose and kidney tissues promotes the progression of kidney damage in obesity. Adipose tissue, which is accumulated in obesity, is a key endocrine organ that produces multiple biologically active molecules, including leptin, adiponectin, resistin, that affect inflammation, and subsequent deregulation of cell function in renal glomeruli that leads to pathological changes. Oxidative stress is also associated with obesity-related renal diseases and may trigger the initiation or progression of renal damage in obesity. In this paper, we focus on inflammation and oxidative stress in the progression of obesity-related glomerulopathy and possible interventions to prevent kidney injury in obesity.